Enhancing public sector efficiency and effectiveness in the Czech Republic - Lewis, Christine (OECD Publishing, 2017)
Spending on public administration itself is relatively low and so are indicators of its performance. Challenges include wastage in public procurement, insufficient management of the investment cycle and high levels of staff turnover. This paper considers ways of building on recent reforms, including better procedures for EU-financed projects and the new Civil Service Act, to raise the efficiency and effectiveness of the public sector. Performance monitoring is underused but could help drive improvements in service delivery. The structure of local government, which includes over 6 200 municipalities, exacerbates the challenges of the public administration by complicating co-ordination and stretching capacity. Accordingly, the second part of the paper focuses on ways of improving the efficiency and quality of public service delivery and realising greater benefits from decentralisation
Keywords: Governance; Economics; Czech Republic